2017
DOI: 10.1101/191999
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-lived rodents reveal signatures of positive selection in genes associated with lifespan and eusociality

Abstract: 20The genetic mechanisms that determine lifespan are poorly understood. Most research has been 21 done on short lived animals and it is unclear if these insights can be transferred to long-lived 22 mammals like humans. Some African mole-rats (Bathyergidae) have life expectancies that are 23 multiple times higher than similar sized and phylogenetically closely related rodents. We obtained 24 genomic and transcriptomic data from 17 rodent species and systematically scanned eleven lineages 25 associated with the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 128 publications
(148 reference statements)
0
4
0
Order By: Relevance
“…The clade containing P. okutanii and A. marissinica was designated as the targeted lineage in the analysis using PosiGene (Sahm et al, 2017a). It has been reported that errors in the analysis are mainly caused by misalignment, which cannot be reduced by multiple test corrections (Sahm et al, 2017b). Therefore, the default pairwise similarity threshold of PosiGene (Sahm et al, 2017a) was applied to remove alignment errors, such as orthologs that were pseudo or poorly aligned, and nominal P-values were directly used to identify positively selected genes (Fletcher and Yang, 2010;Sahm et al, 2017b).…”
Section: Positive Selection Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The clade containing P. okutanii and A. marissinica was designated as the targeted lineage in the analysis using PosiGene (Sahm et al, 2017a). It has been reported that errors in the analysis are mainly caused by misalignment, which cannot be reduced by multiple test corrections (Sahm et al, 2017b). Therefore, the default pairwise similarity threshold of PosiGene (Sahm et al, 2017a) was applied to remove alignment errors, such as orthologs that were pseudo or poorly aligned, and nominal P-values were directly used to identify positively selected genes (Fletcher and Yang, 2010;Sahm et al, 2017b).…”
Section: Positive Selection Analysismentioning
confidence: 99%
“…It has been reported that errors in the analysis are mainly caused by misalignment, which cannot be reduced by multiple test corrections (Sahm et al, 2017b). Therefore, the default pairwise similarity threshold of PosiGene (Sahm et al, 2017a) was applied to remove alignment errors, such as orthologs that were pseudo or poorly aligned, and nominal P-values were directly used to identify positively selected genes (Fletcher and Yang, 2010;Sahm et al, 2017b). If the genes had a P-value below 0.05 and amino acid sites with a bayes empirical bayes (BEB) probability above 0.9, they were regarded as the positively selected genes (Lan et al, 2017(Lan et al, , 2018Sun et al, 2017).…”
Section: Positive Selection Analysismentioning
confidence: 99%
“…In this perspective, a subterranean rodent, the naked mole-rat (Heterocephalus glaber, NMR), and humans represent two species outliers by having an exceptionally long lifespan relatively to their body mass. NMRs are eusocial animals that live in colonies where only a subgroup of animals is devoted to reproduction (usually a queen and one male called pasha) [2]. NMRs exhibit other exceptional traits including lifelong fertility, resistance to infection, high regenerative capacity, resistance to cancer and diabetes, reviewed in [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The assembly of the giant mole-rat transcript catalog was performed based on recently published read data ([23], ENA study PRJEB20584) and the assembly framework FRAMA [24] using default parameters. For rat, mRNA sequences were obtained from RefSeq.…”
Section: Methodsmentioning
confidence: 99%